2021
DOI: 10.1038/s41598-021-95107-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for UV-green dichromacy in the basal hymenopteran Sirex noctilio (Siricidae)

Abstract: A precondition for colour vision is the presence of at least two spectral types of photoreceptors in the eye. The order Hymenoptera is traditionally divided into the Apocrita (ants, bees, wasps) and the Symphyta (sawflies, woodwasps, horntails). Most apocritan species possess three different photoreceptor types. In contrast, physiological studies in the Symphyta have reported one to four photoreceptor types. To better understand the evolution of photoreceptor diversity in the Hymenoptera, we studied the Symphy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…A single electroretinogram study (Peitsch et al, 1992) of four species demonstrated that some Symphyta possess an extra photoreceptor sensitive to red light. This photoreceptor seems to be lost in the rest of the Hymenoptera (Guignard et al, 2021;Peitsch et al, 1992).…”
Section: Common Patterns Knowledge Gaps and Future Prospectsmentioning
confidence: 97%
See 3 more Smart Citations
“…A single electroretinogram study (Peitsch et al, 1992) of four species demonstrated that some Symphyta possess an extra photoreceptor sensitive to red light. This photoreceptor seems to be lost in the rest of the Hymenoptera (Guignard et al, 2021;Peitsch et al, 1992).…”
Section: Common Patterns Knowledge Gaps and Future Prospectsmentioning
confidence: 97%
“…Narrow-band LED and paint could also be used to determine the most attractive colour, if any. In addition, the loss of blue photoreceptor and associated gene in S. noctilio demonstrates that Symphyta possess from two to four photoreceptors in a few closely related families (Guignard et al, 2021). As a result, the Symphyta offer a unique opportunity to study the ecological mechanisms (e.g., feeding habits) underlying the rapid gain and loss of visual opsins and associated photoreceptors.…”
Section: Common Patterns Knowledge Gaps and Future Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of a blue light-sensitive PR is common to many ants and has been noted for several other insect taxa. For example, the loss of the blue-light-sensitive PR has been shown in the basal hymenopteran Sirex noctilio [44] and in most beetle species [21]. The functional significance of this absence raises several questions, which should be addressed in future studies.…”
Section: Eye Morphology and Spectral Sensitivity Of Photoreceptorsmentioning
confidence: 99%